Hubungan antara minat baca dan kemampuan membaca pemahaman dengan keterampilan menulis narasi peserta didik kelas IV sekolah dasar - Fauziah, Khoirunisa; Slamet, Slamet (Didaktika Dwija Indria, 2026)
This study aims to prove the relationship between reading interest and reading comprehension ability with narrative writing skills in public elementary school students in Laweyan sub-district. This study was conducted in 4 public elementary schools in Laweyan sub-district. This type of research is a correlational quantitative study. The research subjects were 158 students. The data collection method was through tests and non-tests. The data analysis techniques used were simple correlation tests and multiple correlation tests. The results of the study showed that there was a significant relationship between reading interest and reading comprehension ability with narrative writing skills in elementary school students. This is evidenced by the simple correlation coefficient value of reading interest with narrative writing skills of 0.421 (t = 5.796 > t table = 1.975). The simple correlation coefficient value of reading comprehension ability with narrative writing skills of 0.620 (t = 9.868 > t table = 1.975). The results of the hypothesis test between reading interest and reading comprehension skills together with narrative writing skills show that the multiple correlation coefficient value is 0.713 (F = 192,534 > F table = 3.05).